Improvement of Student Learning Process and Outcomes About Experience in School Through The Application of The Make A Match Learning Model - Supartini, Dewi Apriyanti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The aim of the research is to improve the process and learning outcomes of the school experience by applying the Make A Match learning model. This type of research uses Classroom Action Research (CAR). Data collection techniques are observation and test learning outcomes. The tools used in data collection were observation sheets and test questions which were then analyzed in a quantitative descriptive way. The results showed an increase in the average process and student learning outcomes. In the pre-cycle conditions the average learning process was in the poor category, then it became a good category in Cycle I, lastly in Cycle II the learning process was in the very good category. Knowledge learning outcomes in pre-cycle conditions were 65.83, then increased to 72.50 and finally in the second cycle to 80.00. The average learning outcomes of skills in pre-cycle conditions students are less skilled in presenting the results of identification of experiences in school.